Engaged Learning Practices of Students in Chemistry Learning - Upadhyaya, Indra Raj; Pokharel, Sharmila; Ghimire, Parasmani (Interdisciplinary Research in Education, 2023)
This study aims to investigate engaged learning practices among undergraduate students in the field of chemistry. The study employed quantitative research design with a total of 88 students from two university campuses in the Kathmandu valley. The research employed a 30-item questionnaire with Likert type, developed based on relevant literature on student engagement, to collect data. The results indicated that the students displayed high levels of behavioural engagement such as staying focused on their chemistry studies, following their teachers' instructions, and completing their assignments and projects on time. Moreover, they were also found to be actively engaged in cognitive practices such as setting learning goals, exhibiting curiosity and interest in chemistry, and putting effort into understanding the concepts. Additionally, the students demonstrated high levels of emotional engagement by exhibiting a desire to understand chemistry, enjoying learning new information, and feeling positive and enthusiastic about the subject. The results of this research hold practical significance for decision makers, science instructors, and future investigators in related areas. The findings have added to the knowledge of the engagement of university level students in their chemistry education. These findings can be used by science instructors and decision makers to create more engaging and effective chemistry learning environments. By providing students with opportunities to engage in active and meaningful learning, instructors can help to ensure that students are successful in their chemistry courses.